Faktor-Faktor Yang Berhubungan Dengan Pernikahan Dini di Wilayah Kerja Puskesmas Sumbang II - Irawati, Sukaefi Nila; Prastika, Dewi Andang; Ulfiana, Elisa (Journal of Midwifery Science: Basic and Applied Research, 2023)
Early marriage is a social phenomenon that continues to occur in Indonesia and the number is still relatively high. Early marriage has a negative impact on health, both for the mother from pregnancy to delivery and for the baby because the reproductive organs are not yet perfect. Early marriage can occur due to factors of knowledge, culture, peers, education, economics and mass media. The aim of this research is to determine the factors associated with early marriage in the Sumbang II Community Health Center Work Area.The type of research used is analytical descriptive with research designcross sectional. The number of samples for this researchas much as34 respondents with the sampling technique used was quota sampling. In collecting data this research used a questionnaire.The results of the univariate test showed that 18 (52.9%) parent’s economic conditions met the minimum wage, 13 (38.2%) had a good level of knowledge and 23 (67.6%) had a good culture. The results of the bivariate test show that there is a relationship between the socio-economic level of parents and the incidence of early marriage p value 0.001, there is a relationship between the level of adolescent knowledge and the incidence of early marriage p value 0.005 and there is a cultural relationship with the incidence of early marriage.p value 0,013. It is hoped that the results of this research will allow midwives to provide socialization on the importance of preventing early marriage not only to teenagers or families but also to the wider community in general so that the data reduces the culture that supports early-age marriage